2021
DOI: 10.1186/s12879-021-06152-1
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume (MPV): new diagnostic indices for co-morbidity of tuberculosis and diabetes mellitus

Abstract: Background Tuberculosis (TB) and type 2 diabetes mellitus (DM) are global health diseases with high morbidity and mortality. Few studies have focused on platelet indices in TB-DM coinfection patients. The objective of this work was to analyze the platelet indices in TB, DM and TB-DM patients to assess the predictive value of the platelet index for the risk of these diseases. Methods In total, 246 patients admitted to our hospital were distributed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Recently, PIs have been thoroughly investigated as novel biomarkers in both acute and chronic diseases [8]. Several studies confirmed the relevance of PI changes in the course of diabetes mellitus (DM) [8][9][10][11], cardiovascular disease (CVD) [8,12,13], cancers [8,9,13], acute surgical conditions [8,14].…”
Section: Of 12mentioning
confidence: 97%
“…Recently, PIs have been thoroughly investigated as novel biomarkers in both acute and chronic diseases [8]. Several studies confirmed the relevance of PI changes in the course of diabetes mellitus (DM) [8][9][10][11], cardiovascular disease (CVD) [8,12,13], cancers [8,9,13], acute surgical conditions [8,14].…”
Section: Of 12mentioning
confidence: 97%
“…Therefore, systemic monocyte markers are clinically used as one of the detection indicators to reflect the severity of the disease and the response to treatment. The new study showed that mean platelet volume (MPV) and plateletcrit (PCT) were significantly decreased in patients with TB-DM, and the sensitivity and specificity of MPV for differentiating TB from TB-DM were 60.8% and 66.4%, respectively [ 61 ]. Studies have shown that MPV and PCT are hopeful as good clinical laboratory markers, which can provide some help for the early diagnosis and prevention of TB-DM.…”
Section: Current Challenges and Future Opportunitiesmentioning
confidence: 99%
“…The role of ALB in PTB has attracted increased attention. Hypoalbuminemia is positively associated with the severity of PTB clinical manifestations of PTB (Xu et al, 2021). In addition, ALB levels were significantly lower in the ATB group than in LTBI (Luo et al, 2022).…”
Section: Diagnostic Performance Of the Scoring System In The Training...mentioning
confidence: 99%